2013
DOI: 10.1128/mcb.00730-13
|View full text |Cite
|
Sign up to set email alerts
|

Rac1 Activation in Podocytes Induces Rapid Foot Process Effacement and Proteinuria

Abstract: The kidney's vital filtration function depends on the structural integrity of the glomerulus, the proximal portion of the nephron. Within the glomerulus, the architecturally complex podocyte forms the final cellular barrier to filtration. Injury to the podocyte results in a morphological change called foot process effacement, which is a ubiquitous feature of proteinuric diseases. The exact mechanism underlying foot process effacement is not known, but recently it has been proposed that this change might reflec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
112
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 109 publications
(118 citation statements)
references
References 36 publications
5
112
1
Order By: Relevance
“…Previous work on RAC1 in kidney disease has focused on its role in the podocyte, where unrestrained activation of RAC1 leads to podocyte effacement and proteinuria (65)(66)(67)(68) and kidney fibrosis, whereby RAC1 alters macrophage migration (69). In contrast, the role of RAC1 in AKI has received little attention.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work on RAC1 in kidney disease has focused on its role in the podocyte, where unrestrained activation of RAC1 leads to podocyte effacement and proteinuria (65)(66)(67)(68) and kidney fibrosis, whereby RAC1 alters macrophage migration (69). In contrast, the role of RAC1 in AKI has received little attention.…”
Section: Discussionmentioning
confidence: 99%
“…5). Although hyperactivation of Rac1 is an accepted pathogenetic model in podocyte disease verified by several independent studies (40,41), there is an ambiguous perception regarding the role of RhoA. Nevertheless, an emerging body of evidence supports the concept of a required balance of these GTPases to maintain cellular function (42).…”
Section: Discussionmentioning
confidence: 99%
“…We and others have previously shown that RAC1 activation in podocytes leads to podocyte foot process effacement and proteinuria in mice (49,50). In addition, excessive macropinocytosis and accumulation of albumin in podocytes has been shown to induce lysosomal dysfunction, podocyte loss, and subsequent glomerulo- sclerosis (15,16,(51)(52)(53)(54)(55).…”
Section: Discussionmentioning
confidence: 99%